General Approach to Metal-Organic Framework Nanosheets With Controllable Thickness by Using Metal Hydroxides as Precursors - Wang, Bingqing; Jin, Jing; Ding, Bin; Han, Xu; Han, Aijuan; Liu, Junfeng (Frontiers in Materials, 2020)
Metal-organic frameworks (MOFs) nanosheets have attracted great attention in recent years due to their unprecedented properties. However, the synthesis of MOF nanosheets with controllable thickness still remains a challenge. In this work, a series of MOF nanosheets, such as CuBDC (BDC = 1,4-benzenedicarboxylate), CoNDC (NDC = naphthalene‐2,6‐dicarboxylate), CoBPDC (BPDC = biphenyl-4,4’-dicarboxylate), NiBDC and ZnTCPP (TCPP = tetrakis(4-carboxyphenyl)porphyrin) were successfully synthesized by using a metal hydroxide precursor approach. Importantly, the thicknesses of the obtained MOF nanosheets can be well regulated by controlling the conversion rate of the metal hydroxides. As a proof-of-concept application, the obtained CuBDC nanosheets were used as the catalyst for olefin epoxidation, which showed much higher catalytic activity compared to the bulk crystals. This work provides an alternative method for the synthesis of various MOF nanosheets, holding great potential for various promising applications.